Avaliação do ciclo de vida da brita para a construção civil: estudo de caso - Rossi, Efigênia (Universidade Federal de São Carlos, 2013)
The civil construction is one of the most important activities for the economic and social development, however it also behaves as a major generator of environmental impacts. The aggregates for construction include crushed stone, sand and gravel and they are the most consumed inputs in the world. About 60 to 80% of the volume of concrete is composed by them and crushed stone has an extensive use. This study aims to wage the Life Cycle Assessment (LCA) of crushed stone in the production of concrete applied in civil construction, through the identification and discussion of quantitative stages of extraction, processing, storage, transport, use and final disposal. In the developing of the methodology we used the standard recommendations of ISO 14040 and 14044, where the study is divided in four parts: Definition of goal and scope, Life Cycle Inventory Analysis (LCI), Life Cycle Impact Assessment (LCIA) and Interpretation. The largest impacts related to the following categories: Human toxicity (soil), Acidification, Nutrient enrichment and Global Warming. The results indicate that the critical steps of the whole life cycle of gravel are, in descending order: Extraction, Transportation from processing to trucks and Final disposal. The emissions from these critical stages correspond to those of higher fuel consumption. As alternatives to mitigate and minimize these impacts we proposed preventive maintenance of equipment and investment in technologies that allow the use of less polluting fuels, such as S50, S10, biodiesel and other biofuels.
Keywords: Construção civil; Avaliação do ciclo de vida dos produtos; Brita; Impacto ambiental; Life Cycle Assessment; Crushed stone; Civil Construction; Environmental impacts; ENGENHARIAS